Incidence and dose-volume relationship of radiation pneumonitis after concurrent chemoradiotherapy followed by durvalumab for locally advanced non-small cell lung cancer. (July 2020) - Saito, Satoshi; Abe, Takanori; Kobayashi, Nao; Aoshika, Tomomi; Ryuno, Yasuhiro; Igari, Mitsunobu; Hirai, Ryuta; Kumazaki, Yu; Miura, Yu; Kaira, Kyoichi; Kagamu, Hiroshi; Noda, Shin-ei; et al.
Highlights: Incidence of grade ≥2 RP was 36% (including grade 3 RP: 5% and grade 5 RP: 3%). Patient characteristics did not significantly differ between patient with grade ≥2 RP and grade ≤1 RP. Dose-volume parameters were significantly higher among patients with grade ≥2 RP. Abstract: Background and purpose: We investigated the incidence and dose-volume relationships of radiation pneumonitis (RP) after concurrent chemoradiotherapy (CCRT) followed by durvalumab for locally advanced non-small-cell lung cancer (LA-NSCLC). Materials and methods: We retrospectively analyzed records of 36 patients with LA-NSCLC who underwent CCRT followed by durvalumab. Incidence of RP was analyzed for correlations with clinical factors and dose-volume parameters of lung in radiotherapy. Results: All patients received 60 Gy in 30 fractions of radiotherapy with concurrent chemotherapy. Over a median follow-up period of 7 months, incidence of grade ≥2 RP was 36% (including grade 3 RP: 5% and grade 5 RP: 3%). Age, sex, Brinkman index, and blood test results did not significantly differ between patients with grade ≥2 RP and grade ≤1 RP. Dose-volume parameters (lung volumes that received 5 Gy, 10 Gy, 20 Gy, 30 Gy, 40 Gy, 50 Gy, and mean lung dose) were significantly higher among patients with grade ≥2 RP compared with patients with grade ≤1 RP. Conclusion: Incidence of grade ≥2 RP was 36% after CCRT followed by durvalumab for LA-NSCLC, but did not significantly differ from those of patients treated with CCRT alone. Lung dose-volume parameters were significantly correlated with RP.